Trait and perceived environmental competitiveness in achievement situations - Elliot, Andrew J.; Jury, Mickaël; Murayama, Kou (Journal of personality, 2018)
Objective Trait and perceived environmental competitiveness are typically studied separately, but they undoubtedly have a joint influence on goal pursuit and behavior in achievement situations. The present research was designed to study them together. We tested the relation between trait and perceived environmental competitiveness, and we tested these variables as separate and sequential predictors of both performance‐based goals and performance attainment. Method In Studies 1a (N = 387 U.S. undergraduates) and 1b (N = 322 U.S. undergraduates), we assessed participants' trait and perceived environmental competitiveness, as well as third variable candidates. In Study 2 (N = 434 MTurk workers), we sought to replicate and extend Study 1 by adding reports of performance‐based goal pursuit. In Study 3 (N = 403 U.S. undergraduates), we sought to replicate and extend Study 2 by adding real‐world performance attainment. The studies focused on both the classroom and the workplace. Results Trait and perceived environmental competitiveness were shown to be positively related and to positively predict separate variance in performance‐approach and performance‐avoidance goal pursuit. Perceived environmental competitiveness and performance‐based goal pursuit were shown to be sequential mediators of the indirect relation between trait competitiveness and performance attainment. Conclusions These studies highlight the importance of attending to the interplay of the person and the (perceived) situation in analyses of competitive striving.